Islamic Management Principles In Human Resource Development: A Conceptual Framework - Ushwa Dwi Masrurah Arifin Bando (Journal of Studies in Academic, Humanities, Research, and Innovation, 2025)
This study aims to formulate a conceptual model of human resource development (HRD) based on Islamic management principles as an integrative approach that combines spirituality, ethics, and professionalism within modern organizational contexts. Islamic HRD is not merely focused on improving technical competencies but also on fostering character, spiritual values, and moral integrity grounded in the principles of tawhid (oneness of God), amanah (trust), ihsan (excellence), and adl (justice). This approach positions humans as khalifah (vicegerents) who hold ethical responsibility in managing organizational resources with fairness, productivity, and sustainability. The findings of this conceptual study reveal that the implementation of Islamic management principles positively influences employee performance, loyalty, psychological well-being, and job satisfaction. The proposed model integrates three core dimensions: (1) Work spirituality, which cultivates the awareness of tawhid and sincerity; (2) Islamic work ethics, emphasizing honesty, responsibility, and justice; and (3) Islamic professionalism, focusing on value-based competency enhancement and productivity. Previous studies affirm that organizations adopting Islamic management principles tend to establish more ethical, harmonious, and adaptive work cultures within the dynamics of the global business environment (Asutay et al., 2022; Al-Saidi & Karim, 2024). Therefore, the conceptual model developed in this study serves as both a theoretical and practical foundation for educational institutions, business organizations, and government agencies in shaping high-quality human resources characterized by integrity, excellence, and holistic well-being.